Developing high performance PA 11/cellulose nanocomposites for industrial-scale melt processing. (1st October 2019) - Venkatraman, Priya; Gohn, Anne M.; Rhoades, Alicyn M.; Foster, E. Johan
Abstract: This study presents methods of developing thermally stable polyamide 11 (PA 11), cellulose nanocrystal (CNCs) composites able to withstand high temperature processing for high performance applications. Thus far, it has been difficult to use cellulose-based composites in industrial applications due to the high temperatures at which the materials would need to be processed. Sulfated CNCs (S–CNCs), the most commercially available CNCs, perform the poorest with respect to being thermally stable at high temperatures. Direct mixing techniques typically used to make these nanocomposites at a lab-scale, even at low concentrations of CNCs, have resulted in poor dispersion and thermal stability of CNCs. However, this paper offers industrially viable methods of fabricating composites that shield these S–CNCs from excessive thermal degradation during processing. We set out to determine the effect of pre-mixing CNCs and the polymer to obtain homogeneous and thermally stable nanocomposites for high temperature processing methods such as compression molding and injection molding. For the PA 11/CNC composites, fabrication through both milling and compounding resulted in reinforcement of the polymer with increased storage modulus in the rubbery plateau, and increased Young's modulus while preserving the toughness of PA 11. Furthermore, the milled samples showed higher stiffness than the compounded samples and surface charge density of the CNCs played a great role in the mechanical properties of the composites as it directly correlates with how well dispersed the composites were. Overall, this work shows the potential of pre-mixing methods to obtain high performance nanocellulose based composites through industrial manufacturing processes. Graphical abstract: Figure showing milling (Mi) and compounding (Co) as two methods of pre-mixing cellulose nanocrystals (CNCs) and PA 11 to produce homogeneously dispersed composite films with their corresponding mechanical properties. PA 11-BG-CNC Mi provided for comparison to indicates a film with poor CNC dispersion due to lower surface charge density. BG refers to CNCs obtained from BlueGoose.Image 1